RANCANGAN ALAT SIMULASI TATA LETAK DAN KONFIGURASI SIRKUIT LAMPU AFL BERBASIS MIKROKONTROLER DI PROGRAM STUDI TEKNIK LISTRIK BANDARA SEKOLAH TINGGI PENERBANG INDONESIA - Andung Luwihono; Zulina Kurniawati; Fredy Edwin Firstnanda (Langit Biru: Jurnal Ilmiah Aviasi)
Airfield Lighting subject is one of the most importance subjects for Airport Electrical Engineering of Indonesia Civil Aviation Institute cadets . There are CBT and AFL in AGL laboratory to support the teaching-learning process as well as the practice of this subject. At the time being, however, there has not been any simulation tool for the layout and circuit configuration of the airport airside. Therefore, the writer designs a simulation tool as a teaching aid/props for the practice of this subject at the laboratory. By having this tool, it is expected that the cadets can do the simulation of the layout and circuit configuration of the airport airside.